Electrochemical and electrical properties of nickel molybdate / carbon material composites - Popovych, O.M.; Budzulyak, I.M.; Kotsyubynsky, V.O.; Yablon, L.S.; Popovych, O.V. (Physics and Chemistry of Solid State, 2021)
The aim of this paper is to establish the optimal content of carbon material in composites with nanocrystal hydrate nickel molybdate. To achieve this, NiMoO4 / C composites with a carbon material content of 1, 5 and 10% by weight (with and without ultrasonic irradiation) were obtained by hydrothermal method. As a result of electrochemical studies, it was found that the maximum specific capacitance of 628 F/g is reached by a composite with a carbon content of 1% after ultrasonic exposure, while this composite shows excellent electrical conductivity, which is 0.47 Ohm-1m-1.